Efficacy and safety of eptinezumab in patients with chronic migraine: PROMISE-2. (31st March 2020) - Lipton, Richard B.; Goadsby, Peter J.; Smith, Jeff; Schaeffler, Barbara A.; Biondi, David M.; Hirman, Joe; Pederson, Susan; Allan, Brent; Cady, Roger
Abstract : Objective: To evaluate the efficacy and safety of eptinezumab, a humanized anti–calcitonin gene-related peptide monoclonal antibody, in the preventive treatment of chronic migraine (CM). Methods: The Prevention of Migraine via Intravenous ALD403 Safety and Efficacy–2 (PROMISE-2) study was a phase 3, multicenter, randomized, double-blind, placebo-controlled, parallel-group study. Adults with CM were randomly assigned to receive IV eptinezumab 100 mg, eptinezumab 300 mg, or placebo administered on day 0 and week 12. The primary endpoint was change from baseline in mean monthly migraine days (MMDs) over weeks 1 to 12. Results: Among treated participants (n = 1, 072), baseline mean number of MMDs was ≈16.1 across groups. Treatment with eptinezumab 100 and 300 mg was associated with significant reductions in MMDs across weeks 1 to 12 compared with placebo (placebo −5.6, 100 mg −7.7, p < 0.0001 vs placebo; 300 mg −8.2, p < 0.0001 vs placebo). Treatment-emergent adverse events (TEAEs) were reported by 43.5% (100 mg), 52.0% (300 mg), and 46.7% (placebo) of patients. Nasopharyngitis was the only TEAE reported for >2% of eptinezumab-treated patients at an incidence of >2% over placebo; it occurred in the 300 mg eptinezumab arm (eptinezumab 9.4%, placebo 6.0%). Conclusion: In patients with CM, eptinezumab 100 and 300 mg was associated with a significant reduction in MMDs from the day after IV administration through week 12, was well tolerated, and demonstrated an acceptable safety profile. Classification of evidence: This study provides Class I evidence that for patients with CM, a single dose of eptinezumab reduces MMDs over 12 weeks of treatment. ClinicalTrials.gov identifier: NCT02974153.